Evaluation of Antioxidant Activity of Balanites Roxburghii Planch. Fruit Extracts (International Journal of Scientific Research and Management (IJSRM), 2019)
Antioxidant potency of fruits of Balanites roxburghii Planch.crude methanol and its fractionated extracts (hexane, ethyl acetate, methanol and water) have been investigated, employing three different established in vitro testing systems, such as scavenging activity on 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals, reducing power assay and β-carotene method. The methanol extract of fruits of Balanites roxburghii Planch.showed the best DPPH scavenging activity with the lowest EC 50 34 μg/ml, followed by the ethyl acetate (EC 50 39 μg/ml), hexane (EC 50 48 μg/ml) and water extract (EC 50 54 μg/ml). The reducing power of Balanites roxburghii Planch. fruit extracts increased steadily with increasing concentrations and varied significantly with different concentrations. The methanol and ethyl acetate extracts appeared to possess the highest significant reducing activity among the extracts. The stronger reducing power in the methanol and ethyl acetate extracts was probably due to the concentration of antioxidant compounds like flavonoids and phenolics in the extract. In the β-carotene bleaching assay, the antioxidant activities of all the fruits extracts gradually increased with increasing concentration of the extracts and varied significantly with different concentrations. The water extract showed the lowest significant antioxidant activity, while the methanol extract showed the highest significant antioxidant activity. The high antioxidant activity of methanol extract tested using β-carotene model may be correlated with the high phenolic content of the methanol extract. In conclusion, antioxidant study suggested that fruits of Balanites roxburghii Planch. are potential source of natural antioxidants. However, further investigations on in vivo antioxidant activities are highly recommended